A computerized digital imaging technique to estimate palm oil quality based on fruit colour. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2007)
Typically palm oil quality is determined in a destructive manner using wet chemical analysis. Such an analysis can be costly, time consuming and error prone. Deterioration of Bleachability Index (DOBI) iS a key Indicator of palm oil quality. An alternative evaluation procedure that combines consistency and reporting accuracy is desirable. One such method is the use of fruit color as an indicator of palm oil quality. A recent study showed that fruit color was significantly correlated with palm oil content (Balasundram et al., 2006). An extension of that work further showed that fruit color was also significantly correlated with DOBI (Balasundram et al., 2006).